4-Phenyl-1, 8-naphthalimides: Brightness and tuning emission over widely visible gamut in different aggregated states. (January 2018) - Qu, Yi; Wang, Linlin; Wu, Jianwei; Rui, Yichuan; Cao, Jian; Xu, Jingli
Abstract: Luminescent organic dyes with tuning emission in widely visible gamut are still interesting challenging. Herein, we report two naphthalimide derivatives (NAPP, NAPTPA ), which can output the variable emission colors covering the whole visible spectra from purple to far-red in aqueous solution. Both naphthalimide derivatives can exhibit bright emission in aqueous solution by introducing a phenyl ring into 4-site of naphthalimide, which acts as a π-bridge in delocalized system and not affects the intramolecular charge transfer process of naphthalimide dyes. Comparison with three analogues (NAPDMP, NAPMOP andNAPDMA ), we evidenced the bright emissions in aqueous solution are from the amorphous emission different from the common crystal emission of naphthalimide dyes. We further fabricated theNAPP andNAPTPA into different nanoparticles matrixes to construct the multi-color toolbox, which could output four colors (purple, blue, green and red) in aqueous solution and yellow emission in crystal. Moreover, the white emission system was obtained through solution doping method. Graphical abstract: A series of 4-phenyl-1, 8-napthalimides were synthesized, for which the fluorescence emission color can be tuned in aqueous solution. The phenyl ring introduced into the 4-position of naphthalimide was used to elicit a bright emission of the dyes in aqueous solution. We have also achieved the modulation of emission colors from purple to far-red by incorporating the dyes with different nanoparticles. Highlights: A series of naphthalimides (NAPs) with phenyl ring at 4-site of the NAP core. Enhanced emissions in aggregated state were achieved in naphthalimide dyes. Red-emission with large Stokes shift in aggregated state was obtained. The modulation of emission colors were achieved from purple to far-red.